MOTIFS OF MANDANA ART IN FASHION PRODUCT - Soni, Sangeeta (International Journal of Research -GRANTHAALAYAH, 2020)
India have a rich Art and Culture heritage, Our cultural and Traditional art speaks about how sensible our Ancestors are, they have Beliefs and reasons behind every art and culture work they do or create. We have varieties of Art forms like painting, sculpture, pottery, and textile arts such as woven silk are one of our Rich Cultural Heritage which makes our India Incredible. One of The Traditional Art is Mandana Art which i used in the redesigning of Mandana Motifs through painting on women’s apparels and high light them by Traditional Embroidery -Kantha Work.